Radiosynthesis and Preliminary Biological Evaluation of (18)F-Fluoropropionyl-Chlorotoxin as a Potential PET Tracer for Glioma Imaging - Zhao, Jing (Contrast Media Mol Imaging, 2018)
PURPOSES: Chlorotoxin can specifically bind to matrix metalloproteinase 2 (MMP-2), which are overexpressed in the glioma. In this work, radiosynthesis of [(18)F]-fluoropropionyl-chlorotoxin ([(18)F]-FP-chlorotoxin) as a novel PET tracer was investigated, and biodistribution in vivo and PET imaging were performed in the C6 glioma model. PROCEDURES: [(18)F]-FP-chlorotoxin was prepared from the reaction of chlorotoxin with [(18)F]-NFB (4-nitrophenyl 2-[(18)F]-fluoropropionate), which was synthesized from multistep reactions. Biodistribution was determined in 20 normal Kunming mice. Small-animal PET imaging with [(18)F]-FP-chlorotoxin was performed on the same rats bearing orthotopic C6 glioma at different time points (60 min, 90 min, and 120 min) after injection and compared with 2-deoxy-2-[(18)F] fluoro-D-glucose ([(18)F]-FDG). RESULTS: [(18)F]-FP-Chlorotoxin was successfully synthesized in the radiochemical yield of 41% and the radiochemical purity of more than 98%. Among all the organs, the brain had the lowest and stable uptake of [(18)F]-FP-chlorotoxin, while the kidney showed the highest uptake. Compared with [(18)F]-FDG, a low uptake of [(18)F]-FP-chlorotoxin was detected in normal brain parenchyma and a high accumulation of [(18)F]-FP-chlorotoxin was found in the gliomas tissue. The glioma to normal brain uptake ratio of [(18)F]-FP-chlorotoxin was higher than that of [(18)F]-FDG. Furthermore, the uptake of [(18)F]-FP-chlorotoxin at 90 min after injection was better than that at 60 min after injection. CONCLUSIONS: Compared with [(18)F]-FDG, [(18)F]-FP-chlorotoxin has a low and stable uptake in normal brain parenchyma. [(18)F]-FP-Chlorotoxin seems to be a potential PET tracer with a good performance in diagnosis of the glioma.